Incidence and Risk Factors for Postoperative Urinary Retention Following Lumbar Spine Fusion. Issue 7 (28th August 2021) - Bowman, John J.; Edwards, Charles C.; Dean, Clayton; Park, Justin; Edwards, Charles C.
Abstract : Study Design: This was a prospective cohort study (observational—retrospective chart review). Objective: The objective of this study was to determine clinical rates and correlations of postoperative urinary retention (POUR) in elective spine decompression and fusion procedures. Summary of Background Data: POUR is a common postoperative complication that often has a major adverse impact on a patient's recovery from elective lumbar spine surgery. The etiology of POUR in most cases is unknown. Patients undergoing lumbar spine surgery are considered to be at increased risk for POUR due to prone positioning during surgery and intraoperative cauda equina nerve root manipulation. Current studies reporting on POUR after elective spine surgery provide limited insight regarding risk factors and effective prevention strategies for this at-risk population. The purpose of this study is to identify risk factors for POUR after elective lumbar spine surgery and strategies for reducing its incidence. Materials and Methods: Two hundred consecutive patients aged 50 years or older undergoing combined lumbar decompression and fusion procedures over a 5-month period at a single institution were prospectively observed. Demographic and clinical data were prospectively recorded, including: medical history, surgical data, medications administered, complications, and postoperative hospital course. Factors correlating with POUR through a univariate analysis with P ≤0.20 were considered for multivariate analysis. Results: POUR occurred in 19 of 200 patients. Those with POUR were more likely to be male (20% vs. 4%, odds ratio=6.2). Administration of scopolamine ( P =0.02), neostigmine ( P =0.01), and the total number of levels operated on ( P =0.02) were found to be independent risk factors for the development of POUR. Length of surgery, surgical level, the performance of an interbody fusion did not have a bearing on the development of POUR ( P >0.05). Discussion: We describe a single institution's experience of POUR incidence in 200 consecutive patients aged 50 years or older undergoing single or multilevel lumbar spine fusion procedures by 1 of 4 surgeons. Specific demographic and clinical risk factors were identified and a codified classification for POUR in a surgical population is presented. The results of this study will help clinicians appropriately counsel patients undergoing elective lumbar fusion about the potential development of POUR. The perioperative administration of scopolamine and neostigmine should be cautiously considered in men over 50 years of age due to the increased POUR risk. Conclusions: Perioperative scopolamine and neostigmine administration in men over 50 should be avoided when possible to minimize the risk of POUR. Level of Evidence: Level III.